Funding validation : a thematic report for the 2016 update of the European inventory on validation of non-formal and informal learning - (:unkn) unknown (Publications Office of the European Union, 2016)
"This thematic report presents an overview of funding sources for validation of non-formal and informal learning and discusses associated issues such as sustainability and accessibility. It is based on data collected for the European inventory on validation of non-formal and informal learning since 2007, and telephone interviews carried out to prepare four detailed case-study examples. The report identifies five different funding sources used by countries across Europe: dedicated public funding from national sources; public funding but not specifically allocated to validation; EU and project funding; mix of public and private sector funding; and fees charged to individual learners. For each of these, it sets out a list of strengths/enablers and barriers/weaknesses. The report concludes with a list of key learning points and suggests that there is scope to look into the issue of validation funding in more detail." (Editor, BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2 Europa; Informelles Lernen; Non-formales Lernen; Anerkennung; Finanzierung; Europäische Union